Hierarchical Attributes of Selected Stakeholders Participation in City Planning and Development: A Case Study of Khon Kaen Smart City, Thailand - Seng, Touch; Hanpachern, Rawee; Bunnarith, Meng; Ampha, Khwanchanok (Journal of Architectural/Planning Research and Studies (JARS), 2022)
This paper aims to determine the hierarchical classification of the attributes of participation used by planners and selected stakeholders in a participatory planning approach for smart city development. It also attempts to contribute to the unsolved question raised by Wandersman Giamartino (1980) that “if participation is so rewarding and effective, why doesn’t everyone participate?” The exploratory sequential mixed method was applied for the data collection procedure. The results of the qualitative approach were used to develop the questionnaires which were conducted with 18 experts/ planners and 111 selected stakeholders. The findings indicated that the interest, influence, and area-based were the key attributes used by planning agency/planners to select the stakeholders to participate in the participatory planning processes. On the other hand, the selected stakeholders relied on the interest, area-based, influence, and urgency to decide to participate in the participatory planning process of Khon Kaen Smart City. Furthermore, the selected stakeholders preferred the on-place-participation rather than e-participation and informal and indirect participation gateways to have an influence on the processes of decision-making.